2021
DOI: 10.1136/tsaco-2021-000682
|View full text |Cite
|
Sign up to set email alerts
|

Brain proteomic changes by histone deacetylase inhibition after traumatic brain injury

Abstract: BackgroundTraumatic brain injury (TBI) is a leading cause of morbidity and mortality. There are currently no cytoprotective treatments for TBI. There is growing evidence that the histone deacetylase inhibitor valproic acid (VPA) may be beneficial in the treatment of TBI associated with hemorrhagic shock and in isolation. We sought to further evaluate the mechanistic underpinnings of this demonstrated efficacy via proteomic analysis of injured brain tissue.MethodsSwine were subjected to TBI via controlled corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Prior studies have demonstrated that TBI induces proteomic changes in the brain that can be potentially modified or inhibited with cytoprotective strategies (130,131). Shultz et al (132) evaluated the proteomic profile of cerebrospinal fluid in a small cohort of severe TBI patients.…”
Section: Proteomicsmentioning
confidence: 99%
“…Prior studies have demonstrated that TBI induces proteomic changes in the brain that can be potentially modified or inhibited with cytoprotective strategies (130,131). Shultz et al (132) evaluated the proteomic profile of cerebrospinal fluid in a small cohort of severe TBI patients.…”
Section: Proteomicsmentioning
confidence: 99%